Hailey-Hailey disease: clinical, diagnostic and therapeutic update - Adriana Maria Porro; Camila Arai Seque; Denise Miyamoto; Diego Vanderlei Medeiros da Nóbrega; Milvia Maria Simões e Silva Enokihara; Claudia Giuli Santi (Sociedade Brasileira de Dermatologia, 2024)
Abstract Hailey-Hailey disease is a rare genodermatosis described in 1939, with an autosomal dominant inheritance pattern, characterized by compromised adhesion between epidermal keratinocytes. It has an estimated prevalence of 1/50,000, with no gender or race predilection. It results from a heterozygous mutation in the ATP2C1 gene, which encodes the transmembrane protein hSPA1C, present in all tissues, with preferential expression in keratinocytes. Mutations in the ATP2C1 gene cause changes in the synthesis of junctional proteins, leading to acantholysis. It usually begins in adulthood, with isolated cases at the extremes of life. It manifests as vesico-bullous lesions mainly in the flexural areas, which develop into erosions and crusts. Chronic lesions may form vegetative or verrucous plaques. Pruritus, a burning feeling and pain are common. It evolves with periods of remission and exacerbation, generally triggered by humidity, friction, heat, trauma and secondary infections. The diagnosis is based on clinical and histopathological criteria: marked suprabasal acantholysis, loosely joined keratinocytes, giving the appearance of a "dilapidated brick wall", with a few dyskeratotic cells. The acantholysis affects the epidermis and spares the adnexal epithelia, which helps in the differential diagnosis with pemphigus vulgaris. Direct immunofluorescence is negative. The main differential diagnoses are Darier disease, pemphigus vegetans, intertrigo, contact dermatitis, and inverse psoriasis. There is no cure and the treatment is challenging, including measures to control heat, sweat and friction, topical medications (corticosteroids, calcineurin inhibitors, antibiotics), systemic medications (antibiotics, corticosteroids, immunosuppressants, retinoids and immunobiologicals) and procedures such as botulinum toxin, laser and surgery. There is a lack of controlled clinical trials to support the choice of the best treatment.